Long non‐coding RNA PVT1: Emerging biomarker in digestive system cancer - Zhou, Dan‐Dan; Liu, Xiu‐fen; Lu, Cheng‐wei; Pant, Om Prakash; Liu, Xiao‐dong (Cell proliferation, 2017)
The digestive system cancers are leading cause of cancer‐related death worldwide, and have high risks of morbidity and mortality. More and more long non‐coding RNAs (lncRNAs) have been studied to be abnormally expressed in cancers and play a key role in the process of digestive system tumour progression. Plasmacytoma variant translocation 1 (PVT1) seems fairly novel. Since 1984, PVT1 was identified to be an activator of MYC in mice. Its role in human tumour initiation and progression has long been a subject of interest. The expression of PVT1 is elevated in digestive system cancers and correlates with poor prognosis. In this review, we illustrate the various functions of PVT1 during the different stages in the complex process of digestive system tumours (including oesophageal cancer, gastric cancer, colorectal cancer, hepatocellular carcinoma and pancreatic cancer). The growing evidence shows the involvement of PVT1 in both proliferation and differentiation process in addition to its involvement in epithelial to mesenchymal transition (EMT). These findings lead us to conclude that PVT1 promotes proliferation, survival, invasion, metastasis and drug resistance in digestive system cancer cells. We will also discuss PVT1's potential in diagnosis and treatment target of digestive system cancer. There was a great probability PVT1 could be a novel biomarker in screening tumours, prognosis biomarkers and future targeted therapy to improve the survival rate in cancer patients.